Literasi Entrepreneurship Untuk Meningkatkan Kemandirian Di Panti Asuhan Putri Aisyiyah Karanganyar - Muhammad Arif Budiman Sucipto; Adzani Fajar Pradana; Aulia Isna Farida; Ayu Nur Rizkiyatul Latifah; Edi Kurniawan; Eka Rizqi Nabila; Ely Fauziyah; Hari Agus Castoro; Moch. Ikhfan Fadlilah; Nesa Dwi Gita Safila; Puji Astuti; Vivi Triyani; Witno Hadi Nurkholis; Moh. Shaefur Rokhman (CV. Multi Kreasi Media, 2024)
An orphanage is a social welfare institution that is responsible for providing substitute services to fulfill the physical, mental and social needs of foster children so that they receive ample and adequate opportunities for personality development in accordance with expectations. Children who live in orphanages are often looked down upon and receive little social support from the community. In these conditions, orphanage children need to be directed and given motivation to become more independent and developed individuals. The aim of this training is to foster entrepreneurial literacy to increase self-reliance among the foster children of the Putri Aisyiyah Karanganyar Orphanage. The method of implementing this leadership project is by providing entrepreneurship training and direct mentoring through several programs, namely training in making mugs, hijabs, ecoprint delivery boxes, training product marketing through the “SPA Karanganyar” marketplace, assessment and career planning group guidance services. The results of the entrepreneurship training program include increasing creativity, improving skills, developing knowledge about career planning, developing an entrepreneurial spirit and independence in the foster children of the Putri Aisyiyah Karanganyar Orphanage. The conclusion from the implementation of this leadership project is that entrepreneurship literacy is an effort to increase independence in the foster children of the Putri Aisyiyah Karanganyar Orphanage.